Lousy chicks: Chewing lice from the Imperial Shag, Leucocarbo atriceps. Issue 3 (December 2017) - Leonardi, María Soledad; Quintana, Flavio
Abstract: Forty-one imperial shag chicks were sampled for lice during the breeding season of 2014 in Punta León, Argentina. We found 2 lice species, Pectinopygus turbinatus infesting the body and Piagetiella caputincisum present in the oral cavity of the birds. This constitutes the first host record for P. turbinatus and the first record for the continental Argentina for P. caputincisum . Ninety-three percent of the chicks were infested by at least one lice species. P . turbinatus was present in all of the lousy chicks, while P. caputincisum infested 84.2% of them. The mean intensity was 29.5 and the range 1–129. There was no difference in prevalence, mean intensity or mean abundance between louse species. However, we found differences among the pattern of infestation of each species. Imperial shag chicks were infested by their parents during their first days of life by P. turbinatus, mainly in nymphal stage and by P. caputincisum as adult lice. Our results showed differences among lice species that could be related to the restrictions that lice from seabirds faced during their life cycle. Graphical abstract: Image 1 Highlights: We record for the first time 2 lice species infesting Imperial shags chicks. Infestation parameters are given and compared for both species. There was no difference in prevalence, mean intensity or abundance between them. We found differences among the patter of infestation of each species.